The Analysis of Formal and Informal Learning in Crossover Learning Strategy to Students’ Activeness at SMP Negeri 29 Makassar - Sitti Mariana; Ummi Khaerati Syam; Hijrah (FKIP Unismuh Makassar, 2023)
This research aimed to analyze the crossover learning strategy in student activeness. The researcher used descriptive qualitative method. The subject of this research was the Seventh grade studets at SMP Negeri 29 Makassar. The researcher used an observation and interviews as instruments to collect the data in this research.Based on the results of the study, the results showed that the types of formal and informal learning in students' crossover learning strategies were formal learning carried out in the classroom while informal learning was outside the classroom (done at home). The implementation of the crossover learning strategy in the learning process is very helpful in achieving the learning atmosphere desired by teachers and students connecting formal (in the classroom) and informal learning (at home) so that students are able to play an active role in the learning process, students are also required to seek more information so that the material conveyed in more detail and clearly and able to solve problems, students are also able to answer questions and discuss with their friends. In this case students are more motivated, more disciplined in learning and responsible.